A critical examination of the consumption‐based accounting approach: has the blaming of consumers gone too far?. (3rd November 2014) - Liu, Lee
Abstract : A series of studies has recently used emissions embodied in net imports (EENI) to argue for the consumption‐based accounting (CBA) approach. These publications have been generating much attention from the media and academia for 'providing an opportunity to inform effective climate policy'. However, policymakers must be cautious when considering if CBA can be used to replace or just to supplement current practice of production‐based accounting (PBA). Terms such as 'carbon leakage', 'emissions transfers', and 'CO2 outsourcing' have been uncritically overused as there is little evidence that EENI is the result of climate policy. Furthermore, CBA overlooks 'insourcing' of polluting industries by producing regions when blaming consumers for emissions. To avoid misinformation, EENI should be called just that. CBA's practicality is limited as it involves more data‐intensive calculations and higher transaction costs than PBA. The success of CBA will rely on consumers to put pressure on producers. Eventually, it is still producers that need to reduce emissions. PBA is more practical by directly placing pressure on producers along with environmental laws and regulations. CBA will be counter‐productive to global emissions control if producers increase emissions due to reduced responsibility over the emissions incurred by the production of their exports. However, CBA could be used to persuade consumers to choose low‐emissions products, support producers' sustainability efforts, and reduce nonbasic consumption. WIREs Clim Change 2015, 6:1–8. doi: 10.1002/wcc.325 This article is categorized under: Climate Economics > Economics of Mitigation The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior